2022
DOI: 10.1001/jamaneurol.2022.1133
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Manifestations of Early-Onset Dementia With Lewy Bodies Compared With Late-Onset Dementia With Lewy Bodies and Early-Onset Alzheimer Disease

Abstract: IMPORTANCE Early-onset dementia, presenting in individuals younger than 65 years, is a diagnosis with significant social and financial implications. The early-onset form of dementia with Lewy bodies (DLB) is poorly understood. OBJECTIVE To investigate clinical features that distinguish early-onset DLB (onset and diagnosis at age <65 years) from late-onset DLB (onset at age Ն65 years) and from early-onset Alzheimer disease (AD) dementia. DESIGN, SETTING, AND PARTICIPANTS This is a retrospective case-control st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
1
Order By: Relevance
“…Of note, subclinical depressive symptoms in ageing are linked with neurodegeneration biomarkers in the precuneus, PCC and fronto-temporal regions [27]. Previous studies reported the presence and intensity of depressive mood speci cally characterized the clinicopathological cohort of EO-DLB [5]. While we did not nd differences between EO and LO-DLB in neuropsychiatric presentations, depression, and apathy can be observed and linked to the above-reported evidence when a large cohort of subjects would be included.…”
Section: Discussioncontrasting
confidence: 48%
See 1 more Smart Citation
“…Of note, subclinical depressive symptoms in ageing are linked with neurodegeneration biomarkers in the precuneus, PCC and fronto-temporal regions [27]. Previous studies reported the presence and intensity of depressive mood speci cally characterized the clinicopathological cohort of EO-DLB [5]. While we did not nd differences between EO and LO-DLB in neuropsychiatric presentations, depression, and apathy can be observed and linked to the above-reported evidence when a large cohort of subjects would be included.…”
Section: Discussioncontrasting
confidence: 48%
“…Early onset (EO) dementia refers to a condition starting before the age of 65, often characterized by more marked behavioral and psychiatric symptoms, and a higher mortality than late-onset (LO) dementia [2]. EO and LO dementia with Lewy bodies (DLB) are similar in terms of core clinical symptoms (i.e., visual hallucinations, parkinsonism, uctuating cognition, and REM sleep behavior disorder (RBD) [3,4], however, LO-DLB present more severe memory de cits than EO-DLB, while EO-DLB has a quicker decline and neuropsychiatric features at the beginning [5]. The EO-DLB has been poorly investigated yet, however, some speci c prodromal clinical features are reported, namely a history of depression that can predate an early onset of DLB [6].…”
Section: Introductionmentioning
confidence: 99%
“…A recent clinicopathological study showed that EO-DLB and LO-DLB are largely similar in core symptoms and with a comparable distribution of limbic and neocortical Lewy pathology [5]. However, LO-DLB patients present more amnestic de cits that were accounted for by AD co-pathology, and EO-DLB can be predated by history of depression [5]. The present study shows similarities between EO-DLB and LO-DLB in terms of clinical core symptom presentations and major brain hypometabolism hallmarks.…”
Section: Discussionmentioning
confidence: 99%
“…EO and LO dementia with Lewy bodies (DLB) are similar in terms of core clinical symptoms (i.e., visual hallucinations, parkinsonism, uctuating cognition, and REM sleep behavior disorder (RBD) [3,4], however, LO-DLB present more severe memory de cits than EO-DLB, while EO-DLB has a quicker decline and neuropsychiatric features at the beginning [5]. The EO-DLB has been poorly investigated yet, however, some speci c prodromal clinical features are reported, namely a history of depression that can predate an early onset of DLB [6].…”
Section: Introductionmentioning
confidence: 99%
“…Parkinson’s disease (PD) is a common chronic progressive neurodegenerative disease, ranking as the second most common neurodegenerative disease only after Alzheimer’s disease. The exact cause of PD is still unclear, and most scholars currently believe that PD is pathologically related to the degeneration of dopamine neurons in the substantia nigra . Nowadays, the diagnosis of PD currently relies on medical history and clinical symptoms.…”
Section: Introductionmentioning
confidence: 99%